Situation Report: Hungary, 4 May 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. CC Plenum An Interview with TU Secretary-General Sandor Gaspar University Admission Difficulties Uj Iras and Avant-Gardism The Private Artisan: Development and Problems Development of Hungarian-French Economic Relations Problems of Vegetable Production in Hungary Fodder Supply Difficulties